2017
DOI: 10.1016/j.bbadis.2017.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Berberine-induced cardioprotection and Sirt3 modulation in doxorubicin-treated H9c2 cardiomyoblasts

Abstract: A B S T R A C TDoxorubicin (DOX) is one of the most widely used anti-neoplastic agents. However, treatment with DOX is associated with cumulative cardiotoxicity inducing progressive cardiomyocyte death. Sirtuin 3 (Sirt3), a mitochondrial deacetylase, regulates the activity of proteins involved in apoptosis, autophagy and metabolism. Our hypothesis is that pharmacological modulation by berberine (BER) pre-conditioning of Sirt3 protein levels decreases DOX-induced cardiotoxicity. Our results showed that DOX indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 92 publications
0
47
0
Order By: Relevance
“…More recently, it was reported that BBR could alleviate high glucose-induced podocyte apoptosis via autophagy 15 . In addition, BBR can stimulate autophagy in various tissues including heart 16 , lungs 17 and hepar 18 , however, this has not been shown in the NP. Considering that oxidative stress, apoptosis and inflammatory activation are all elements of IVDD pathology, we hypothesize that BBR may utilize autophagy to prevent the formation of IVDD.…”
Section: Introductionmentioning
confidence: 93%
“…More recently, it was reported that BBR could alleviate high glucose-induced podocyte apoptosis via autophagy 15 . In addition, BBR can stimulate autophagy in various tissues including heart 16 , lungs 17 and hepar 18 , however, this has not been shown in the NP. Considering that oxidative stress, apoptosis and inflammatory activation are all elements of IVDD pathology, we hypothesize that BBR may utilize autophagy to prevent the formation of IVDD.…”
Section: Introductionmentioning
confidence: 93%
“…For example, dexrazoxane, an iron chelating agent against iron-mediated oxidative stress, is the cardio-protective medicine approved by FDA in July 1995 for preventing anthracycline-induced cardiotoxicity, and now has been widely applied in the clinical practice (Padegimas et al, 2020). In addition, numerous natural antioxidants serve as adjuvant therapies to reduce drug-induced cardiotoxicity, such as berberine, epigallocatechin-3-gallate, and resveratrol (Coelho et al, 2017;Yu et al, 2018).…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…Polydatin, a monocrystalline and a polyphenolic drug extracted from the traditional Chinese herb Polygonum cuspidatum , protects cardiomyocytes against myocardial infarction injury by upregulating autophagy and improving mitochondrial biogenesis via SIRT3 activity [ 116 ]. Berberine decreases DOX-induced cardiotoxicity by activating SIRT3 [ 117 ]. Honokiol, a natural biphenolic compound derived from the bark of magnolia trees, blocks and reverses cardiac hypertrophy by activating SIRT3 [ 76 , 118 ].…”
Section: Therapeutic Applicationmentioning
confidence: 99%